Slavic Paganism in Medieval Christian Writings: Ink, Cross, and Pagan Gods - Dynda, Jiří (East Central and Eastern Europe in the Middle Ages, 450-1450 Series, 2025)
This volume provides a fresh look at how medieval Christian texts portrayed Slavic paganism. By combining insights from texts, archaeology, and ethnography within the broader framework of religious studies, it deepens our understanding of Christian-pagan interactions in the Middle Ages.